Paris COP 21: Power that Speaks the Truth?. Issue 6 (1st November 2016) - Morgan, Jamie
Abstract: In this paper, I set out some of the key aspects of the Paris COP 21 Climate Change Agreement. The Paris Agreement was initially reported as a major success. However, this was in so far as many thought any kind of agreement at all was unlikely, and because the Agreement includes Article 2: an aspiration to maintain average global temperature increases to significantly less than 2°C. I then ask the question: if the Paris Agreement is a success of sorts, has anything fundamental changed in order to translate the conditional success of achieving an agreement into an actual success that will realise the goals of the Agreement? I address this in terms of early assessment of trends and the Nationally Determined Contributions, how responsibility is positioned in the Agreement, and the political economy context, which has called forth the need for an agreement.